Implementasi Literasi Digital Dalam Strategi Pemasaran Di Desa Wisata Baturusa Mewujudkan Ketahanan Ekonomi - Kusumah, Echo Perdana; Fauzi, Padlun; Mahendra, Fazaldi; Pasaribu, Waldimer (Indonesian Journal of Dedication and Educations, 2024)
Digital literacy is an important aspect in increasing the competitiveness of tourist villages, especially in Baturusa Tourism Village. This study aims to evaluate the implementation of digital literacy as a marketing strategy in supporting community economic resilience. The method used is a qualitative approach with socialization techniques, practical training, interview and discussion, and evaluation. The results show that the use of social media and other digital platforms increases market reach and promotion efficiency, despite obstacles such as limited internet access and low levels of technology adoption. This study recommends strengthening digital infrastructure and ongoing training to maximize the positive impact of digital literacy on the village economy.